A water washable antistatic abrasion resistant fiber and method of making same
Patent Information
- Application Number
- CN202610708210.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-21
- Publication Date
- 2026-10-20
AI Technical Summary
但该专利中短纤在力学性能上存在明显不足,整体强度偏低,难以满足面料所需的高强力要求,干断裂强度直接决定纤维的耐摩擦、抗撕裂与织造加工稳定性,湿断裂强度是纤维耐水洗、潮湿环境下强力保持的关键指标,断裂伸长率影响纤维柔韧性、抗疲劳性与面料尺寸稳定性,体积电阻率则直接表征纤维抗静电效果与电荷消散能力,四项参数共同决定纤维在耐磨、耐水洗、长效抗静电场景下的适用性,而现有竹炭基抗静电粘胶纤维难以同时满足高干强、高湿强、适宜伸长率与稳定低电阻率的综合要求,无法适配高端功能纺织品对耐用性与功能性的严苛需求
1、本发明采用枯草芽孢杆菌、黄孢原毛平革菌两步梯度发酵,先分解半纤维素与易降解组分,再深度降解残余木质素,使竹炭粉质地更均匀、颗粒圆润、与粘胶相容性提升,提高纤维干断裂强度与湿断裂强度;同时增强与石墨、纺丝液的界面相容性,从而改善纤维耐磨性与抗静电耐久性。
Smart Images

Figure REF-OBJ-1779344160248-000001
Abstract
Description
Technical Field
[0001] This invention belongs to the field of textile fiber technology, specifically relating to a water-resistant, antistatic, and abrasion-resistant fiber and its preparation method. Background Technology
[0002] With the upgrading of the modern textile industry and the continuous expansion of the application scenarios of functional textiles, water resistance, high abrasion resistance, and long-lasting antistatic properties have become the core performance requirements of textiles. At the same time, fabrics are prone to fiber breakage, dimensional instability, and strength reduction during frequent friction, bending, and repeated washing, which directly reduces the product's service life and application reliability.
[0003] Regenerated cellulose fibers, with their skin-friendly, breathable, and moisture-wicking properties, are widely used in functional textiles. Chinese patent CN103556280B discloses an antistatic bamboo charcoal viscose fiber and its preparation method, which has good breathability and moisture absorption, a soft hand feel, and significant and long-lasting antistatic effects. However, the short fibers in this patent have significant shortcomings in mechanical properties, with overall low strength, making it difficult to meet the high strength requirements of fabrics. Dry breaking strength directly determines the fiber's abrasion resistance, tear resistance, and weaving stability. Wet breaking strength is a key indicator of fiber's resistance to washing and strength retention in humid environments. Breaking elongation affects fiber flexibility, fatigue resistance, and fabric dimensional stability. Volume resistivity directly characterizes the fiber's antistatic effect and charge dissipation ability. These four parameters together determine the fiber's applicability in abrasion-resistant, washable, and long-lasting antistatic scenarios. Existing bamboo charcoal-based antistatic viscose fibers cannot simultaneously meet the comprehensive requirements of high dry strength, high wet strength, suitable elongation, and stable low resistivity, making them unsuitable for the stringent durability and functionality requirements of high-end functional textiles. Summary of the Invention
[0004] The purpose of this invention is to provide a water-resistant, antistatic, and abrasion-resistant fiber and its preparation method, while improving the dry and wet breaking strength and breaking elongation of bamboo charcoal viscose fiber, exhibiting excellent antistatic properties, good water resistance, and abrasion resistance.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a water-resistant, washable, antistatic, and abrasion-resistant fiber includes the following steps: (1) Add water to bamboo powder, add Bacillus subtilis, stir evenly, and carry out the first aerobic fermentation; continue to add Protozoa chrysophagus for the second aerobic fermentation, sterilize, dry, and obtain fermented bamboo powder. Carbonize the fermented bamboo powder under an inert atmosphere; cool, crush, and obtain fermented bamboo charcoal powder. (2) Mix graphite powder, water and dispersant, stir evenly to obtain graphite solution; mix fermented bamboo charcoal powder, water, dispersant, thickener and alkaline aqueous solution to obtain bamboo charcoal solution; (3) Mix the graphite solution and the bamboo charcoal solution to obtain an antistatic bamboo charcoal solution; (4) Fibers were obtained by spinning using an antistatic bamboo charcoal solution and viscose spinning solution; (5) The fibers are successively subjected to plasticizing traction, washing, desulfurization, bleaching, oiling, drying and humidification to obtain water-resistant antistatic and wear-resistant fibers.
[0006] Existing technologies use ordinary bamboo powder or single / mixed microbial fermentation to prepare bamboo charcoal. However, the degradation of lignin and hemicellulose in the bamboo powder is insufficient, resulting in weak interfacial bonding with the viscose matrix and low dry and wet strength of the fibers, making it difficult to meet the requirements for wear resistance and durability. This invention employs a two-step gradient fermentation using Bacillus subtilis and Proteobacterium chrysosporium, effectively improving both dry and wet mechanical strength. Analysis shows that the microbial fermentation of this invention first decomposes hemicellulose and easily degradable components, and then deeply degrades residual lignin, thereby improving the compatibility of bamboo charcoal with viscose and increasing the dry and wet breaking strength of the fibers.
[0007] Preferably, the conditions for the first aerobic fermentation are: aerobic fermentation at 30-35℃ for 3-4 days.
[0008] Preferably, the conditions for the second aerobic fermentation are: aerobic fermentation at 30-35℃ for 2-3 days.
[0009] Preferably, the live cell mass ratio of Bacillus subtilis and Phanerochaete chrysosporium is (5-6):(3-4).
[0010] Preferably, the graphite particle size range is 5μm-15μm.
[0011] The study found that gradient fermentation with two strains could not completely solve the problem of low fiber elongation at break. This invention, through precise ratio and synergistic fermentation of two strains, can further improve fiber elongation at break. The reason is that under these conditions, bamboo powder and graphite can synergistically ferment. Specific fermentation can gently and selectively degrade lignin and hemicellulose in bamboo powder, while highly preserving and purifying the original microfibril skeleton of bamboo cellulose. This results in bamboo charcoal powder obtained through subsequent carbonization having a high aspect ratio fibrous morphology, abundant surface-active functional groups, and a microcrystalline structure. When combined with graphite powder, it can act as a flexible bridge and interfacial anchoring center, effectively solving the problems of poor dispersibility and weak interfacial bonding of graphite powder in viscose fibers. Therefore, while improving conductivity and wear resistance, it significantly improves elongation at break.
[0012] Preferably, the total amount of Bacillus subtilis and Protozoa chrysospora accounts for 0.8-1.2% of the bamboo powder mass.
[0013] The preferred carbonization conditions are as follows: First stage: heat up from room temperature to 200-250℃ and hold for 1-2 days; Second stage: heat up to 400-450℃ and hold for 2-3 days; Third stage: heat up to 850-900℃ and hold for 2-3 days.
[0014] Preferably, the heating rate in the first stage is 1-2℃ / min; the heating rate in the second stage is 1-2℃ / min; and the heating rate in the third stage is 2-3℃ / min.
[0015] Existing carbonization technologies suffer from limited processing methods, resulting in insufficient development of the conductive structure in bamboo charcoal. When combined with graphite, they fail to form a continuous conductive pathway, leading to poor antistatic properties and weak mechanical properties. This invention employs a three-stage gradient carbonization process, which synergizes with the initial gradient fermentation and graphite blending. This precisely controls the pore structure and graphitization degree of the bamboo charcoal, reducing volume resistivity while simultaneously ensuring both wet and dry strength and elongation at break. The reason for this is that fermentation provides a uniform porous precursor, gradient carbonization enables the bamboo charcoal to form a complete conductive microcrystalline and pore structure, and efficient bonding with graphite creates a continuous and stable conductive network. The synergy of these three processes ensures antistatic performance without compromising mechanical properties, achieving a simultaneous improvement in high strength, high elongation, and low resistivity.
[0016] Preferably, the drying conditions in step (5) are: heating to 130-135°C and holding at that temperature until constant weight.
[0017] The water-resistant, antistatic, and abrasion-resistant fiber obtained by the aforementioned preparation method.
[0018] Preferably, the water-resistant, antistatic, and abrasion-resistant fiber has a dry breaking strength of 3.0-3.1 cN / dtex, a wet breaking strength of 2.0-2.2 cN / dtex, an elongation at break of 20.7-21.1%, and a volume resistivity of 1.3-1.5 × 10⁻⁶. 8 Ω・cm.
[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This invention employs a two-step gradient fermentation process using Bacillus subtilis and Protozoa chrysophagus to first decompose hemicellulose and easily degradable components, and then to deeply degrade residual lignin. This results in bamboo charcoal powder with a more uniform texture, rounded particles, and improved compatibility with viscose, thereby enhancing the dry and wet breaking strength of the fiber. Simultaneously, it strengthens the interfacial compatibility with graphite and spinning solution, thereby improving the fiber's abrasion resistance and antistatic durability.
[0020] 2. This invention achieves a synergistic effect with graphite powder of a specific particle size through precise ratio and synergistic fermentation of two strains, which can improve fiber breaking elongation.
[0021] 3. This invention employs a three-stage gradient carbonization process, which works synergistically with the initial gradient fermentation and graphite compounding to precisely control the pore structure and graphitization degree of bamboo charcoal, reducing volume resistivity while simultaneously ensuring dry and wet strength and elongation at break. The synergy of these three processes ensures antistatic properties without compromising mechanical properties, achieving a simultaneous improvement in high strength, high elongation, and low resistivity. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] All raw materials used in the following embodiments of the present invention are commercially available products: The strain of Bacillus subtilis has the accession number CICC10732 and originates from the China Industrial Microbial Culture Collection Center. The viable count in the powder is 20 billion CFU / g.
[0024] The strain number of *Phanerochaete chrysosporium* is CICC14076, obtained from the China Industrial Microbial Culture Collection Center. The viable count in the mycelial powder is 20 billion CFU / g.
[0025] MOA3PK, an antistatic agent, is manufactured by Nantong Zhanyi Chemical Co., Ltd.
[0026] Cellulose thickener, sodium carboxymethyl cellulose, Changshu Weiyi Technology Co., Ltd.: PC500.
[0027] Example 1
[0028] This embodiment provides a water-resistant, washable, antistatic, and abrasion-resistant fiber, the preparation method of which includes the following steps: (1) Fresh mature bamboo is crushed into bamboo powder raw material with a mesh size of 20; water is added to adjust the moisture content to 55wt%, sterilized, Bacillus subtilis is added, the amount of Bacillus subtilis accounts for 0.6% of the mass of bamboo powder raw material, stirred evenly, and aerobic fermentation at 35℃ for 3 days with an aeration rate of 1.0vvm; Phanerochaete chrysosporium is added, the amount of Phanerochaete chrysosporium accounts for 0.4% of the mass of bamboo powder raw material, aerobic fermentation at 35℃ for 2 days, sterilized, and dried to a moisture content of 5% to obtain fermented bamboo powder, and the fermented bamboo powder is carbonized: first stage: the heating rate is 1℃ / min to 200℃, and the temperature is kept for 1 day; second stage: the heating rate is 1℃ / min to 400℃, and the temperature is kept for 3 days; third stage: the heating rate is 2℃ / min to 850℃, and the temperature is kept for 2 days; cooled to room temperature and crushed to a D50 of 0.8μm to obtain fermented bamboo charcoal powder; (2) Weigh out graphite powder and add it to water at 10 times the weight of the graphite powder. Then add sodium dodecyl sulfate dispersant at 2.3% of the weight of the graphite powder and stir until uniform to obtain graphite solution (solution A). Mix fermented bamboo charcoal powder and water at a mass ratio of 1:5. While stirring, add 1.5% sodium polyacrylate dispersant (by weight of bamboo charcoal powder), 2% cellulose thickener (by weight of bamboo charcoal powder), and a 30wt% NaOH aqueous solution to make the sodium hydroxide content in solution B reach 5wt%. Stir evenly, grind until the particle size is ≤0.5μm, and let stand for 60 minutes to defoam, thus obtaining the bamboo charcoal solution (solution B). (3) Calculate the amount of solution A and solution B based on the graphite content of 4% and the fermented bamboo charcoal powder content of 7% in the antistatic wear-resistant fiber. Add solution A to solution B under stirring conditions, continue stirring for 30 minutes, stop stirring, let stand for 90 minutes, and after standing, obtain the antistatic bamboo charcoal solution (solution C). The spinning solution was obtained by dissolving and maturing cellulose xanthate; the spinning solution had a cellulose content of 9.0 wt%, a NaOH content of 5.0 wt%, a maturation degree of 9.0 mL, and a viscosity of 50 mPa·s.
[0029] (4) Using the traditional process, a static mixer is used to send the C solution and spinning solution into the mixer through metering pumps. The flow rate of the C solution entering the mixer is controlled to be 1.2:1 with the flow rate of the viscose to obtain a mixture. The mixture is then sent directly to the spinning machine for spinning. The temperature of the spinning mixture is 15℃. The composition of the coagulation bath is: H2SO4 110g / L, Na2SO4 260g / L, ZnSO4 3g / L, Al2(SO4) 36g / L, with the remainder being water. The temperature of the coagulation bath is 45℃, the spinning speed is 50m / min, and the total draw ratio is 135%. The spinning mixture is extruded through the spinneret into the coagulation bath and instantly solidifies into filaments. The filaments travel a distance of 2.0m in the coagulation bath, completing the initial forming and obtaining fibers. (5) Using traditional processes, the fibers are sequentially subjected to plasticizing and drawing, washing, desulfurization, bleaching, oiling, drying, and humidification. The temperature of the plasticizing bath is 90℃, containing 10g / L of H2SO4, with the remainder being water. The first-stage drawing is 25%, the second-stage drawing is 15%, and the fibers are cut to 38mm. 40℃ soft water is used for washing, and the fibers are rinsed countercurrently until neutral. 3g / L Na2S aqueous solution is used for desulfurization at 80℃ for 15min. 0.2g / L aqueous solution containing available chlorine is used at room temperature for 10min, followed by rinsing with soft water until chlorine and sulfur are removed. Antistatic oil and antistatic agent MOA3PK are used for oiling at a bath ratio of 1:5 at 40℃ for 10min. The drying conditions are: heating to 130℃ to constant weight; and placing the fibers in an environment of 20℃ and 65% relative humidity for 24h to ensure uniform internal moisture, thus obtaining washable antistatic and abrasion-resistant fibers.
[0030] Example 2
[0031] This embodiment provides a water-resistant, washable, antistatic, and abrasion-resistant fiber, the preparation method of which includes the following steps: (1) Fresh mature bamboo is crushed into bamboo powder raw material with a mesh size of 20; water is added to adjust the moisture content to 55wt%, sterilized, Bacillus subtilis is added, the amount of Bacillus subtilis accounts for 0.5% of the mass of bamboo powder raw material, stirred evenly, and aerobic fermentation at 35℃ for 4 days with an aeration rate of 1.0vvm; Phanerochaete chrysosporium is added, the amount of Phanerochaete chrysosporium accounts for 0.3% of the mass of bamboo powder raw material, aerobic fermentation at 35℃ for 3 days, sterilized, and dried to a moisture content of 5% to obtain fermented bamboo powder, and the fermented bamboo powder is carbonized: first stage: the heating rate is 2℃ / min to 250℃, and the temperature is kept for 1 day; second stage: the heating rate is 2℃ / min to 450℃, and the temperature is kept for 2 days; third stage: the heating rate is 2℃ / min to 900℃, and the temperature is kept for 2 days; cooled to room temperature and crushed to a D50 of 0.8μm to obtain fermented bamboo charcoal powder; (2) Weigh out graphite powder and add it to water at 10 times the weight of the graphite powder. Then add sodium dodecyl sulfate dispersant at 2.3% of the weight of the graphite powder and stir until uniform to obtain graphite solution (solution A). Mix fermented bamboo charcoal powder and water at a mass ratio of 1:5. While stirring, add 1.5% sodium polyacrylate dispersant (by weight of bamboo charcoal powder), 2% cellulose thickener (by weight of bamboo charcoal powder), and a 30wt% NaOH aqueous solution to make the sodium hydroxide content in solution B reach 5wt%. Stir evenly, grind until the particle size is ≤0.5μm, and let stand for 60 minutes to defoam, thus obtaining the bamboo charcoal solution (solution B). (3) Calculate the amount of solution A and solution B based on the graphite content of 4% and the fermented bamboo charcoal powder content of 7% in the antistatic wear-resistant fiber. Add solution A to solution B under stirring conditions, continue stirring for 30 minutes, stop stirring, let stand for 90 minutes, and after standing, obtain the antistatic bamboo charcoal solution (solution C). The spinning solution was obtained by dissolving and maturing cellulose xanthate; the spinning solution had a cellulose content of 9.0 wt%, a NaOH content of 5.0 wt%, a maturation degree of 9.0 mL, and a viscosity of 50 mPa·s.
[0032] (4) Using the traditional process, a static mixer is used to send the C solution and spinning solution into the mixer through metering pumps. The flow rate of the C solution entering the mixer is controlled to be 1.2:1 with the flow rate of the viscose to obtain a mixture. The mixture is then sent directly to the spinning machine for spinning. The temperature of the spinning mixture is 15℃. The composition of the coagulation bath is: H2SO4 110g / L, Na2SO4 260g / L, ZnSO4 3g / L, Al2(SO4) 36g / L, with the remainder being water. The temperature of the coagulation bath is 45℃, the spinning speed is 50m / min, and the total draw ratio is 135%. The spinning mixture is extruded through the spinneret into the coagulation bath and instantly solidifies into filaments. The filaments travel a distance of 2.0m in the coagulation bath, completing the initial forming and obtaining fibers. (5) Using traditional processes, the fibers are sequentially subjected to plasticizing and drawing, washing, desulfurization, bleaching, oiling, drying, and humidification. The temperature of the plasticizing bath is 90℃, containing 10g / L of H2SO4, with the remainder being water. The first-stage drawing is 25%, the second-stage drawing is 15%, and the fibers are cut to 38mm. 40℃ soft water is used for washing, and the fibers are rinsed countercurrently until neutral. 3g / L Na2S aqueous solution is used for desulfurization at 80℃ for 15min. 0.2g / L aqueous solution containing available chlorine is used at room temperature for 10min, followed by rinsing with soft water until chlorine and sulfur are removed. Antistatic oil and antistatic agent MOA3PK are used for oiling at a bath ratio of 1:5 at 40℃ for 10min. The drying conditions are: heating to 130℃ to constant weight; and placing the fibers in an environment of 20℃ and 65% relative humidity for 24h to ensure uniform internal moisture, thus obtaining washable antistatic and abrasion-resistant fibers.
[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that the bacterial strain is replaced with the mixed bacterial strain from Example 2 of the method for preparing textile fibers by microbial fermentation, as described in CN107287271A: *Pseudomonas stearothermii*: *Bacillus licheniformis*: *Bacillus subtilis*: *Trichoderma reesei*: selenium-enriched yeast: *Micrococcus roseus* = 1:3:4:5:1:0.5. All strains are commercially available.
[0034] Fresh, mature bamboo is crushed into 20-mesh bamboo powder raw material; water is added to adjust the moisture content to 55wt%, sterilized, and mixed inoculum is added, with the amount of mixed inoculum accounting for 1.0% of the mass of the bamboo powder raw material. The mixture is stirred evenly and fermented aerobically at 35℃ for 5 days with an aeration rate of 1.0 vvm; sterilized and dried to a moisture content of 5% to obtain fermented bamboo powder. The fermented bamboo powder is then carbonized in the following stages: First stage: heating rate of 1℃ / min to 200℃, holding for 1 day; Second stage: heating rate of 1℃ / min to 400℃, holding for 3 days; Third stage: heating rate of 2℃ / min to 850℃, holding for 2 days; cooled to room temperature and crushed to a D50 of 0.8μm to obtain fermented bamboo charcoal powder.
[0035] Comparative Example 2 The difference between this comparative example and Example 1 is as follows: Fresh, mature bamboo was crushed into 20-mesh bamboo powder raw material; water was added to adjust the moisture content to 55 wt%, sterilized, and Bacillus subtilis and P. chrysosporium were added, with Bacillus subtilis accounting for 0.6% of the bamboo powder raw material mass and P. chrysosporium accounting for 0.4% of the bamboo powder raw material mass. The mixture was stirred evenly and fermented aerobically at 35℃ for 5 days with an aeration rate of 1.0 vvm; sterilized and dried to a moisture content of 5% to obtain fermented bamboo powder. The fermented bamboo powder was then carbonized: First stage: heating rate of 1℃ / min to 200℃, holding for 1 day; Second stage: heating rate of 1℃ / min to 400℃, holding for 3 days; Third stage: heating rate of 2℃ / min to 850℃, holding for 2 days; cooled to room temperature and crushed to a D50 of 0.8 μm to obtain fermented bamboo charcoal powder.
[0036] Comparative Example 3 The difference between this comparative example and Example 1 is the number of fermentation days.
[0037] Fresh, mature bamboo was crushed into 20-mesh bamboo powder raw material. Water was added to adjust the moisture content to 55 wt%, and the mixture was sterilized. Bacillus subtilis was added at a rate of 0.6% of the bamboo powder raw material mass. The mixture was stirred evenly and fermented aerobically at 35°C for 1 day with an aeration rate of 1.0 vvm. Phanerochaete chrysosporium was then added at a rate of 0.4% of the bamboo powder raw material mass. The mixture was fermented aerobically at 35°C for 4 days, sterilized, and dried to a moisture content of 5% to obtain fermented bamboo powder. The fermented bamboo powder was then carbonized in the following stages: Stage 1: Heating rate was 1°C / min to 200°C and held for 1 day; Stage 2: Heating rate was 1°C / min to 400°C and held for 3 days; Stage 3: Heating rate was 2°C / min to 850°C and held for 2 days. The mixture was cooled to room temperature and crushed to a D50 of 0.8 μm to obtain fermented bamboo charcoal powder.
[0038] Comparative Example 4 The difference between this comparative example and Example 1 is that the amount of bacterial strain used is different.
[0039] Fresh, mature bamboo was crushed into 20-mesh bamboo powder raw material. Water was added to adjust the moisture content to 55 wt%, and the mixture was sterilized. Bacillus subtilis was added at a rate of 0.4% of the bamboo powder raw material mass. The mixture was stirred evenly and fermented aerobically at 35℃ for 3 days with an aeration rate of 1.0 vvm. Phanerochaete chrysosporium was then added at a rate of 0.6% of the bamboo powder raw material mass. The mixture was fermented aerobically at 35℃ for 2 days, sterilized, and dried to a moisture content of 5% to obtain fermented bamboo powder. The fermented bamboo powder was then carbonized in the following stages: Stage 1: Heating rate was 1℃ / min to 200℃ and held for 1 day; Stage 2: Heating rate was 1℃ / min to 400℃ and held for 3 days; Stage 3: Heating rate was 2℃ / min to 850℃ and held for 2 days. The mixture was cooled to room temperature and crushed to a D50 of 0.8 μm to obtain fermented bamboo charcoal powder.
[0040] Comparative Example 5 The difference between this comparative example and Example 1 is that the carbonization temperature is different.
[0041] The fermented bamboo powder is carbonized in the following stages: First stage: the temperature is increased to 300℃ at a rate of 1℃ / min and held for 1 day; Second stage: the temperature is increased to 500℃ at a rate of 1℃ / min and held for 3 days; Third stage: the temperature is increased to 950℃ at a rate of 2℃ / min and held for 2 days.
[0042] Comparative Example 6 The difference between this comparative example and Example 1 is that the carbonization heating rate is different.
[0043] The fermented bamboo powder is carbonized in the following stages: First stage: heating rate is 5℃ / min to 200℃, and the temperature is maintained for 1 day; Second stage: heating rate is 5℃ / min to 400℃, and the temperature is maintained for 3 days; Third stage: heating rate is 10℃ / min to 850℃, and the temperature is maintained for 2 days.
[0044] Comparative Example 7 This comparative example is the short fiber product of Example 5 in CN103556280B, "Antistatic Bamboo Charcoal Viscose Fiber and its Preparation Method".
[0045] Performance testing The performance of the fibers (short fibers) prepared in Examples 1-2 and Comparative Examples 1-7 was tested: 1. The dry breaking strength and wet breaking strength of the fiber were tested in accordance with GB / T14463-2022 "Viscose Staple Fiber".
[0046] 2. Test the elongation at break according to GB / T14337-2022 "Test Method for Tensile Properties of Short Fibers".
[0047] 3. The volume resistivity was determined in accordance with GB / T14342-2015 "Test Method for Specific Resistivity of Short Chemical Fibers".
[0048] The test results are shown in Table 1.
[0049] Table 1 Performance Test Results As shown in Table 1, the water-resistant, antistatic, and abrasion-resistant fibers prepared in Examples 1-2 have a dry breaking strength of 3.0-3.1 cN / dtex, a wet breaking strength of 2.0-2.2 cN / dtex, a breaking elongation of 20.7-21.1%, and a volume resistivity of 1.3-1.5 × 10⁻⁶. 8 The Ω·cm value indicates that all properties are at a high level. This demonstrates that the present invention, through a two-step gradient fermentation process using Bacillus subtilis and Protozoa chrysospora, synergistic effect of the two strains, and a three-stage gradient carbonization process, produces bamboo charcoal powder with a uniform pore structure and excellent dispersibility. This results in a stable and continuous conductive network with graphite, while also exhibiting strong interfacial bonding with the viscose matrix. Consequently, the fiber possesses high mechanical strength, suitable elongation at break, and excellent antistatic properties, demonstrating superior overall performance compared to existing technologies.
[0050] In Comparative Example 1, altering the fermentation microbial system led to uneven degradation of bamboo powder, increased structural defects in bamboo charcoal, decreased dry / wet breaking strength and elongation at break, and increased volume resistivity, indicating that specific dual-strain gradient fermentation is crucial for bamboo powder modification. In Comparative Example 2, simultaneous dual-strain fermentation resulted in microbial antagonism, reduced decomposition efficiency, and decreased mechanical and antistatic properties, demonstrating that stepwise gradient fermentation can maximize microbial synergy. In Comparative Example 3, altering the fermentation times of the two stages resulted in insufficient pretreatment of the bamboo powder, leading to a deterioration in all properties. In Comparative Example 4, changing the ratio of the two microbial strains resulted in an imbalance in the synergistic effect, leading to a deterioration in the structure and dispersibility of the bamboo charcoal and a decrease in its performance. In Comparative Example 5, changing the carbonization temperature resulted in poor development of the conductive and mechanical structures of the bamboo charcoal, with a decrease in strength, elongation, and antistatic properties, indicating that the gradient carbonization temperature range affects the quality of bamboo charcoal. In Comparative Example 6, changing the carbonization heating rate resulted in cracks and uneven porosity inside the bamboo charcoal, leading to a decrease in mechanical properties and the stability of the conductive pathways. In Comparative Example 7, the fibers prepared by the existing technology had low strength, low elongation, and high resistivity.
[0051] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a water-washable, antistatic, and abrasion-resistant fiber, characterized in that, Includes the following steps: (1) Add water to bamboo powder, add Bacillus subtilis, stir evenly, and carry out the first aerobic fermentation; continue to add Protozoa chrysospora for the second aerobic fermentation, sterilize, dry, and obtain fermented bamboo powder. Carbonize the fermented bamboo powder; cool, crush, and obtain fermented bamboo charcoal powder. (2) Mix graphite powder, water and dispersant, stir evenly to obtain graphite solution; mix fermented bamboo charcoal powder, water, dispersant, thickener and alkaline aqueous solution to obtain bamboo charcoal solution; (3) Mix the graphite solution and the bamboo charcoal solution to obtain an antistatic bamboo charcoal solution; (4) Fibers were obtained by spinning using an antistatic bamboo charcoal solution and viscose spinning solution; (5) The fibers are successively subjected to plasticizing traction, washing, desulfurization, bleaching, oiling, drying and humidification to obtain water-resistant antistatic and wear-resistant fibers.
2. The method for preparing water-washable, antistatic, and abrasion-resistant fibers according to claim 1, characterized in that, The conditions for the first aerobic fermentation are: 30-35℃ aerobic fermentation for 3-4 days.
3. The method for preparing the water-washable, antistatic, and abrasion-resistant fiber according to claim 2, characterized in that, The conditions for the second aerobic fermentation are: aerobic fermentation at 30-35℃ for 2-3 days.
4. The method for preparing the water-washable, antistatic, and abrasion-resistant fiber according to claim 3, characterized in that, The live cell mass ratio of Bacillus subtilis and Phanerochaete chrysosporium was (5-6):(3-4).
5. The method for preparing the water-washable, antistatic, and abrasion-resistant fiber according to claim 1, characterized in that, The total amount of Bacillus subtilis and Phanerochaete chrysosporium accounted for 0.8-1.2% of the bamboo powder mass.
6. The method for preparing the water-washable, antistatic, and abrasion-resistant fiber according to claim 1, characterized in that, The carbonization conditions are as follows: First stage: heat up from room temperature to 200-250℃ and keep warm for 1-2 days; Second stage: heat up to 400-450℃ and keep warm for 2-3 days; Third stage: heat up to 850-900℃ and keep warm for 2-3 days.
7. The method for preparing the water-washable, antistatic, and abrasion-resistant fiber according to claim 6, characterized in that, The heating rate in the first stage is 1-2℃ / min; the heating rate in the second stage is 1-2℃ / min; and the heating rate in the third stage is 2-3℃ / min.
8. The method for preparing water-washable, antistatic, and abrasion-resistant fibers according to claim 1, characterized in that, The particle size of graphite ranges from 5 μm to 15 μm.
9. A water-resistant, antistatic, and abrasion-resistant fiber prepared by the preparation method according to any one of claims 1-8.
10. The water-resistant, antistatic, and abrasion-resistant fiber according to claim 9, characterized in that, The dry breaking strength of the water-resistant, antistatic, and abrasion-resistant fiber is 3.0-3.1 cN / dtex, the wet breaking strength is 2.0-2.2 cN / dtex, the elongation at break is 20.7-21.1%, and the volume resistivity is 1.3 × 10⁻⁶. 8 -1.5×10 8 Ω・cm.
Citation Information
Patent Citations
An antistatic bamboo charcoal viscose fiber and its preparation method
CN103556280B
Method of preparing fibers for textiles by microbiological fermentation
CN107287271A